Neonicotinoid Pesticides Are More Toxic to Honey Bees at Lower Temperatures: Implications for Overwintering Bees - Saleem, Muhammad Shoaib; Huang, Zachary Y.; Milbrath, Meghan O. (Frontiers in Ecology and Evolution, 2020)
The honey bee (Apis mellifera) is an important pollinator as well as an important test model for pesticide effects on other insect pollinators. Honey bees have been experiencing high mortality in both the United States and worldwide. Pesticide exposure has been identified as one of the many stressors causing this mortality. Effects of various pesticides have been measured for multiple responses such as learning, memory performance, feeding activity, and thermoregulation. These studies were conducted at many different temperatures (11–35°C); however, few studies compared toxicity of the same pesticide to bees at different temperatures. It is possible that the same pesticide might show different toxicity to honey bees at different temperatures. To reveal such potential interactions, we administered low doses of two neonicotinoid insecticides (imidacloprid and thiamethoxam) at three different temperature scenarios (35°C, 24°C, and a varying temperature) and determined the effects on honey bee survivorship. We discovered that honey bees are much more sensitive to the neonicotinoid pesticides imidacloprid and thiamethoxam at a constant 24°C or at a varying temperature (night at 13°C and day at 24°C) compared to bees at 35°C. These results suggest that honey bee colonies during winter time will be more sensitive to pesticides. Doses of neonicotinoids that are safe to colonies during summer might kill them during the winter time.